Analyzing TPACK Competence among Pre-Service Indonesian Language Teachers: A Quantitative Case Study - Silvia Marni; Harry Andheska; Sainee Tamphu; Abdul Wahid; Astri Widyaruli Anggraeni; Trisna Helda; Muhammad Aliman (STAI Hubbulwathan Duri, 2026)
The integration of digital technology in education requires pre-service teachers to develop strong Technological Pedagogical Content Knowledge (TPACK). However, empirical studies examining TPACK implementation in Indonesian language teacher education—particularly in regional universities—remain limited. This study aims to examine the TPACK competencies of pre-service Indonesian language teachers and identify demographic factors influencing their technology integration capabilities. This study employed a quantitative approach using an online questionnaire distributed to 133 pre-service Indonesian language teachers at Universitas PGRI Sumatra Barat who had completed microteaching courses. The collected data were analyzed using descriptive statistics to determine TPACK competency levels and to examine variations based on demographic variables, including gender, academic level, and duration of technology use. The findings indicate that participants demonstrated a moderate level of TPACK competency (mean score = 2.69; 67.25%). Variations in competency were observed across demographic categories. The highest competency levels were found among second-year students and those with 3–4 years of technology experience, suggesting potential developmental windows for optimal TPACK acquisition. Gender differences were also evident: male participants showed higher scores in most TPACK domains, while female participants performed better in integrated TPACK. The results highlight that TPACK development may not follow a strictly linear progression. Instead, certain periods during teacher education may serve as optimal phases for strengthening technology integration skills. These findings underscore the importance of implementing structured and targeted technology integration strategies within teacher education curricula to support effective TPACK development among pre-service teachers.